Innate antiviral signalling in the central nervous system. - Bowie, Andrew; Carty, Michael (My University, 2014)
The innate immune system mediates protection against neurotropic viruses capable of infecting the central nervous system (CNS). Neurotropic viruses include herpes simplex virus (HSV), West Nile virus (WNV), rabies virus, La Crosse virus, and poliovirus. Viral infection triggers activation of pattern recognition receptors (PRRs) such as Toll-like receptors (TLRs), retinoic acid-inducible gene 1 (RIG-I) like receptors (RLRs), nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs), and cytosolic DNA sensors. Although originally characterised in peripheral immune cells, emerging evidence points to important roles for these PRRs in cells of the CNS. Here, we review recent advances in our understanding of the mechanisms by which these PRRs provide protection against neurotropic viruses, and discuss instances in which these responses become detrimental and cause immunopathology in the CNS.
PUBLISHED
Keywords: Toll-like receptors; antiviral immunity; central nervous system; retinoic acid-inducible gene 1; stimulator of interferon genes; Immunology, Inflammation & Infection